A Making Authentic Deed of Distribution of Inheritance to Land by a Notary Public - Dicky Ardiansyah; Anis Mahdurohatun; Munsharif Abdul Chalim (Jurnal Akta, 2021)
The making of a certificate of inheritance is carried out by a different official, which is based on the population group, there are three officials who are authorized to make a certificate of inheritance, namely the Notary, the Heritage Hall (BHP), or made by the heirs themselves on paper witnessed by the Head of Village / Village Head and strengthened by the Head District. This writing aims to analyze the process of making authentic deeds of distribution of inheritance of land rights, the obstacles faced by the notary and their solutions. Researchers used legal research methods with a normative juridical approach. The data source came from secondary data. This writing is analyzed qualitatively using the analysis knife of Islamic justice theory, legal certainty theory, and inheritance distribution theory. The results showed that: 1) The process of making an inheritance distribution deed begins with the making of an inheritance certificate (SKW), which is the first step in carrying out the process of distributing inheritance to land in Jepara. The next step is: joint heirs before the notary in the presence of 2 (two) witnesses, bringing the documents that have been determined, the notary checks the files, certificates carried by both parties. The Official for Making Land Deeds (PPAT) makes a will or a certificate of inheritance. The will shall be signed by the heir and the PPAT (made in two copies). 2) PPAT obstacles in the process of distributing inheritance of land rights, namely: legal substance, legal structure, and legal culture. Solutions to obstacles, namely: Consulting and asking for help from government officials in the local village or sub-district. The government needs to disseminate information to the community. Provide information regarding the procedure and procedures for registration as well as incomplete document documents to the applicant.